Perbandingan Kadar Lemak, Protein Dan Bahan Kering Tanpa Lemak (BKTL) Pada Susu Sapi Segar Di Kota Kediri Dan Kabupaten Kediri - Miarsono Sigit; Wahyu Rafida Putri; Junianto Wika Adi Pratama (Universitas Islam Kadiri, 2021)
The aimed of the study to determine the difference fat content, protein content and Solid Non Fat (SNF) in fresh cow’s milk in Kediri City and Kediri District. This study used fresh cow's milk from Friesian Holstein crossbreed as many as 40 samples, 20 samples from Kediri City and 20 samples from Kediri District. The type of research was a survey with a quantitative approach. Sampling was carried out used quota sampling by comparing the fat content, protein content and Solid Non Fat (SNF) in fresh cow's milk from Kediri City and Kediri District. The data analyzed by T-test. After testing milk using Lactoscan then calculated and found the average fat content from the City of Kediri was 2.9525 mg / dl and the averaged fat content from Kediri District was 3.2860 mg/dl. The averaged of the protein content from Kediri City was 2.1025 mg/dl and the protein content from Kediri Distict 2.1795 mg/dl. The average Solid Non Fat (SNF) from the City of Kediri is 5.6620 mg/dl and the averaged Solid Non Fat (SNF) from Kediri Regency is 5.8690 mg/dl. The result showed that no significant difference (P>0,05) in fat content, protein content and Solid Non Fat (SNF).